Target therapy for high-risk neuroblastoma treatment: integration of regulatory and scientific tools is needed - Ceci, Adriana; Conte, Rosa; Didio, Antonella; Landi, Annalisa; Ruggieri, Lucia; Giannuzzi, Viviana; Bonifazi, Fedele (Frontiers in Medicine, 2023)
Introduction. Several new active substances (ASs) targeting neuroblastoma (NBL) are under study. We aim to describe the developmental and regulatory status of a sample of ASs targeting NBL, to underline the existing regulatory gaps to product development, and to discuss possible improvements. Methods. The developmental and regulatory status of the identified ASs targeting NBL was investigated by searching for preclinical studies, clinical trials (CTs), marketing authorizations, pediatric investigation plan (PIP), waiver, orphan designation and other regulatory procedures. Results. One hundred and eighty-eight ASs were identified. Of these, 55 were considered ‘not under development’ without preclinical or clinical studies. Preclinical studies were found for 115 ASs of which, 54 were associated with a medicinal product. Two hundred and eighty-three CTs (as monotherapy or in combination) were identified for 70 ASs. Of these, 52% were phase 1, 1/2, 2 aimed to PK/PD/dosing activity. The remaining ones also included efficacy. Phase 3 studies were limited. Studies were completed for 14 ASs and suspended for 11. The highest rate of ASs involved in CTs was observed in the RAS-MAPK-MEK and VEGF groups. Thirty-seven ASs were granted with a PIP, 14 including NBL, 41 ASs with a waiver and 18 with both PIPs and waivers, with the PIP covering pediatric indications different from the adult ones. In almost all the PIPs, preclinical studies were required, together with early phase CTs often including efficacy evaluation. Two PIPs were terminated with negative studies results, 8 are in progress. Variations in the SmPC were made for larotrectinib sulfate/Vitrakvi® and entrectinib/Rozyltrek® with the inclusion of a new indication. For both, the related PIPs are still ongoing. Orphan designation has been largely adopted, while PRIME designation has been less implemented. Discussion. Several ASs entered in early phase CTs but less than 1 out of 4 is included in a regulatory process and only 2 were granted a pediatric indication extension. Our results confirm that it is necessary to identify a more efficient, less costly and time-consuming ‘pediatric developmental model’ integrating predictive preclinical studies and innovative clinical studies designs. Furthermore, stricter integration between scientific and regulatory efforts should be promoted.